IMPROVING STUDENTS’ PRONUNCIATION THROUGH ENGLISH SONG - Wulandari, Dian (UG Journal, 2021)
Some teachers do not teach pronunciation very well in their class. The more frequently teach reading and grammar than pronunciation. Therefore, students’ ability in pronouncing the words is still low and they feel difficult to pronounce the words given by the teacher. It makes the students feel afraid of making mistakes in pronouncing the words. It happens because the students do not have any habit in learning pronunciation in their class and they are not interested of learning pronunciation. The objective of this research is to improve students’ pronunciation ability by using English song media. English songs can be used by English teachers to teach pronunciation in every level. This research uses classroom action research. It was conducted in three cycles and each cycle has four steps; planning, acting, observing, and reflecting. The data gained from observation and students’ score test of pronunciation. The researcher took a class consists of thirty students with three cycles. The result showed that there is improvement in students’ test scores after the researcher conduct three cycles of research. The result was taken from students’ scores in pronunciation. It showed that teaching pronunciation by using English songs is very effective in the teaching-learning process